Viking Theme Festivals: Stakeholders Perspective in the North of Portugal and Galicia - Pedro LIBERATO; André SILVA; Dália LIBERATO (Communications of International Proceedings, 2020)
In Galicia and the north of Portugal, from the 8th to the 11th century, Viking and Norman peoples were present. Initially through piracy activities that they developed and later through their support in crusades and holy wars. Local communities felt the need to revitalise these memories through thematic festivals, to assess the possibility of developing these events and to understand which strategies should be used to ensure the cultural sustainability of festivals. In this study the qualitative method was used, where the participants who are part of the scientific community, event organizers and tourism promoters with links to Viking thematic festivals in the Euro-region of Northern Portugal and Galicia were selected. The main results show that the biggest challenge for those responsible for organizing Viking thematic festivals is to maintain the levels of authenticity, following the principles of conservation of intangible heritage.
Keywords: Viking; Heritage; Authenticity; Theme Festivals; North of Portugal; Galicia.